Legal Protection of Students Who Are Victims of Abuse of Educators in Asahan District in Terms of Law No. 35 Of 2014 Concerning Child Protection - Yani Zandroto; Hafsah Hafsah; Hasan Matsum (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2020)
This study examines the violence of educators against their students that occurred in the Asahan District. This case is interesting to study because educators should not perpetrate violence against their students, and students should receive guaranteed protection from such acts of violence. The focus of the problems studied is: 1) forms of legal protection provided by Law No. 35 of 2014 for students, and 2) the role of the government, school supervisors and education staff in providing legal protection for students who experience acts of abuse by educators in the school environment. This type of research is qualitative with a juridical and normative approach. This study found that the role of the Asahan District Government in efforts to prevent acts of abuse and violence against students/children both within the school environment and outside the school environment is by establishing a Child-Friendly District (LKA) as a form of concern for child growth and development and safe and comfortable life For children. The role of the Asahan Regency Government in efforts to prevent acts of abuse and violence against students/children both within the school environment and outside the school environment is by establishing a Child-Friendly District (LKA) as a form of concern for child growth and development and safe and comfortable life for children. Legal protection for children that has been carried out, if based on Law No. 35 of 2014, more serious efforts are needed so that the realization of the values of the law can be realized properly.